Waste-to-energy nexus: A sustainable development. (December 2020) - Sharma, Surbhi; Basu, Soumen; Shetti, Nagaraj P.; Kamali, Mohammadreza; Walvekar, Pavan; Aminabhavi, Tejraj M.
Abstract: An upsurge in global population due to speedy urbanization and industrialization is facing significant challenges such as rising energy-demand, enormous waste-generation and environmental deterioration. The waste-to-energy nexus based on the 5R principle (Reduce, Reuse, Recycle, Recovery, and Restore) is of paramount importance in solving these Gordian knots. This review essentially concentrates on latest advancements in the field of 'simultaneous waste reduction and energy production' technologies. The waste-to-energy approaches (thermal and biochemical) for energy production from the agricultural residues are comprehensively discussed in terms environmental, techno-economic, and policy analysis. The review will assess the loopholes in order to come up with more sophisticated technologies that are not only eco-friendly and cost-effective, but also socially viable. The waste-to-energy nexus as a paradigm for sustainable development of restoring waste is critically discussed considering future advancement plans and agendas of the policy-makers. Graphical abstract: Image 1 Highlights: Waste-to-energy technologies have been comprehensively reviewed. Thermal route of waste treatment provides char, oil and syngas as products. Biochemical treatment of waste yields biogas, ethanol and hydrogen energy. Using agricultural waste to obtain energy can solve 'crop residue burning' issue. The environmental and techno-economic analysis was briefly discussed.